Hydroxyapatite Coatings for Biomedical Applications - Zhang, Sam (Taylor & Francis, 2013)
Hydroxyapatite coatings are of great importance in the biological and biomedical coatings fields, especially in the current era of nanotechnology and bioapplications. With a bonelike structure that promotes osseointegration, hydroxyapatite coating can be applied to otherwise bioinactive implants to make their surface bioactive, thus achieving faster healing and recovery. In addition to applications in orthopedic and dental implants, this coating can also be used in drug delivery. Hydroxyapatite Coatings for Biomedical Applications explores developments in the processing and property characterization and applications of hydroxyapatite to provide timely information for active researchers and newcomers alike. In eight carefully reviewed chapters, hydroxyapatite experts from the United States, Japan, Singapore, and China present the latest on topics ranging from deposition processes to biomedical applications in implants and drug delivery. This book discusses: Magnetron sputtering and electrochemical deposition The modification of hydroxyapatite properties by sol-gel deposition to incorporate other elements found in natural bones, such as zinc, magnesium, and fluorine The use of pure hydroxyapatite in drug delivery applications The growth or self-assembly of hydroxyapatite on shape memory alloy Hydroxyapatite composite coatings-with carbon nanotubes, titanium dioxide (TiO2), and others-on the titanium alloy Offering valuable insights and a wealth of data, including numerous tables and figures, this is a rich source of information for research on hydroxyapatite coatings. Each chapter also covers material that provides an accessible stepping stone for those who are new to the field.